Postmortem examination of COVID‐19 patients reveals diffuse alveolar damage with severe capillary congestion and variegated findings in lungs and other organs suggesting vascular dysfunction. Issue 2 (5th July 2020) - Menter, Thomas; Haslbauer, Jasmin D; Nienhold, Ronny; Savic, Spasenija; Hopfer, Helmut; Deigendesch, Nikolaus; Frank, Stephan; Turek, Daniel; Willi, Niels; Pargger, Hans; Bassetti, Stefano; Leuppi, Joerg D; et al.
Abstract : Aims: Coronavirus disease 2019 (COVID‐19), caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), has rapidly evolved into a sweeping pandemic. Its major manifestation is in the respiratory tract, and the general extent of organ involvement and the microscopic changes in the lungs remain insufficiently characterised. Autopsies are essential to elucidate COVID‐19‐associated organ alterations. Methods and results: This article reports the autopsy findings of 21 COVID‐19 patients hospitalised at the University Hospital Basel and at the Cantonal Hospital Baselland, Switzerland. An in‐corpore technique was performed to ensure optimal staff safety. The primary cause of death was respiratory failure with exudative diffuse alveolar damage and massive capillary congestion, often accompanied by microthrombi despite anticoagulation. Ten cases showed superimposed bronchopneumonia. Further findings included pulmonary embolism ( n  = 4), alveolar haemorrhage ( n  = 3), and vasculitis ( n  = 1). Pathologies in other organ systems were predominantly attributable to shock; three patients showed signs of generalised and five of pulmonary thrombotic microangiopathy. Six patients were diagnosed with senile cardiac amyloidosis upon autopsy. Most patients suffered from one or more comorbidities (hypertension, obesity, cardiovascular diseases, and diabetes mellitus). Additionally, there was an overall predominance of males and individuals with blood group A (81% and 65%, respectively). All relevant histological slides are linked as open‐source scans in supplementary files. Conclusions: This study provides an overview of postmortem findings in COVID‐19 cases, implying that hypertensive, elderly, obese, male individuals with severe cardiovascular comorbidities as well as those with blood group A may have a lower threshold of tolerance for COVID‐19. This provides a pathophysiological explanation for higher mortality rates among these patients.